KEPATUHAN PEMERINTAH DESA DALAM PENGGUNAAN DANA DESA BERDASARKAN PERATURAN PEMERINTAH RI NO. 22 TAHUN 2015 - Deny Prasetyo, Suharno & Bambang Widarno (Universitas Slamet Riyadi, 2017)
The purpose of this study was to analyze the compliance of the village administration in the use of village funds in terms of aspects of planning and budgeting, implementation, administration, reporting, and accountability in Government Regulation No. 22 Year 2015. The research used the case study method, the type of data used quantitative and qualitative data, the data source used primary data. Methods of data collection used questionnaires, observation and documentation. Data analysis technique used is descriptive statistical analysis. In conclusion: 1) Compliance with the village government in the use of village funds in terms of planning and budgeting in the village Tegalombo and Banaran village categorized quite good, it is planning and budgeting management of village finances is done through Deliberation Village Planning. 2) Compliance village government in the use of village funds in terms of implementation in the village Tegalombo categorized as poor, while in village Banaran categorized quite good, it is because of limited human resources capacity of the village on the use techonology accounting. 3) Compliance village government in the use of funds in terms of administration in the village of Tegalombo and Banaran village categorized quite good, that the administration conducted by the Village Treasurer already make record every revenue and expenditure did close the books each month end in an orderly manner. 4) Compliance village government in the use of village funds in terms of reporting and accountability in the village Tegalombo in the category, while in the village of Banaran categorized quite good, that the village chief had to submit a report realization APBDes to the Regent of the consolidated first half. While the realization APBDes accountability report prepared by the head of the village consists of revenues, expenditures, and financing.Keywords: government compliance village, village funds, planning and budgeting, implementation, administration, reporting and accountability.